QUANTITATIVE METHOD ANALYSIS LEVEL OF COMMUNITY PARTICIPATION IN HUMAN RESOURCE DEVELOPMENT - Reinald stevianes. L; Muammar Khadafi; Iswarijaya; Syarif Ahmad; Wan Iwan Darmawan; Nurhandika Sepvia Putri; Uci Liharyanti; Santi Sihombing; Novita Nasution; Ongky Parmadhie Putra (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
This research aims to determine the level of community participation in Tanjungpiang regarding Human Resources development. The sampling technique used simple random sampling with a sample of 75 people. Data collection techniques use observation, interviews, literature study and questionnaires. The research results show that; 1) the level of community participation is 56.8%, which is in the poor/less influential category, 2) Human Resources development is 58.5%, which is in the poor/less influential category, 3) the level of community participation in Human Resources development.